PRAKSIS INTERNALISASI KARAKTER KEMANDIRIAN DI PONDOK PESANTREN YATIM PIATU ZUHRIYAH YOGYAKARTA - Nashihin, Husna (J-PAI: Jurnal Pendidikan Agama Islam, 2018)
This article is a field research that uses the phenomenology approach. Data analysis used in tihis article is qualitative analysis. Zuhriyah Islamic Boarding School is an orphanage-specific boarding school. The internalization of independence character for santri is one of the main goals. This research has the following backgrounds; First, there is still a moral decadence in society today. Second, it is necessary to develop character education using habituation methods based on activities. Third, Zuhriyah Islamic Boarding School has implemented character habituation based on the management of pesantren activities. Fourth, the Zuhriyah Islamic Boarding School is an orphanage-specific boarding school, so there is a demand for santri to be more independent. Fifth, the character of independence becomes the main character instilled in this pesantren. Sixth, there is no research on the habituation of the character of independence in the Zuhriyah Islamic Boarding School. Furthermore, there are three urgent things to study, namely; first, the concept of character education at Zuhriyah Islamic Boarding School. Second, the basic of the internalization of the character of the santri in Zuhriyah Islamic Boarding School. Third, the habituation of the character of the independence of the santri at the Zuhriyah Islamic Boarding School. The concept of character education in the pesantren is in line with the theoretical conception of character education. There are seven activities in Zuhriyah Islamic Boarding School, namely; formal education and yellow book teaching, recitation and routine mujahadah, incidental activities, donations, cooking and cathering for serving food, management of kyai’s houses, and cleanliness of the boarding. Habituation of the character of independence is carried out by managing all this seven pesantren activities independently.Keywords: Character Habituation; Independence of Santri; Zuhriyah Islamic Boarding School